Tokelau tā tatau – Tokelau tattoo : a reconnection to cultural identity : an exhibition report presented in partial fulfilment of the requirements for the degree Masters in Māori Visual Arts at Massey University, Palmerston North, New Zealand - Kirifi, Jack Fati (Massey University, 2024)
This exhibition report presents the art of Tokelau tā tatau or traditional Tokelau tattoo as a journey of reconnection to Tokelau cultural identity through contemporary Tokelau art. The loss of Tokelau tā tatau in the mid 1800’s due to missionary influence disconnected the art and symbolism of tā tatau as an expression of Tokelau cultural identity. My framework traces a journey of reconnection, bridging the past to the present to confront and remove the cultural amnesia surrounding tā tatau, which was once central to Tokelau cultural identity. The historical series and tupuna portraits in this report re-establishes the significance of tā tatau and its relevance in the contemporary landscape of Tokelau cultural identity. Contemporary Tokelau art has influenced the re-emergence of Tokelau tā tatau motifs within Tokelau communities today. This report reflects my personal journey as a New Zealand born Tokelau artist reconnecting to Tokelau tā tatau through my art practice.
Keywords: 451318 Pacific Peoples visual arts and crafts